Evaluating Students’ Perception of Teaching Learning Computer Programming: A Study in a Bruneian Technological University - Seyal, Afzaal H.; ., Yeo Sy Mey (Journal of Education and Vocational Research, 2015)
The present study is part of one of the pioneering government funded research, conducted in one of the institutions of higher learning in Brunei Darussalam. The study validates the existing instrument through survey (factor analysis) among cohort of students in a programming class. The study results not only endorse the reasons of declining the art and science of teaching/learning computer programming but also have brought an interesting finding of pedagogy. The results indicate that teaching and learning strategies are more teacher-centered (mean=3.85) rather than student-centered (mean = 2.87). This is in contrast to modern approach of teaching-learning, where problem-based or constructivist approach dominates. Further 67% of the students considered lack of motivation, 80% considered the curriculum is less practical and 50% thought it was more teacher-centered, as key reasons of this decline. Based on the findings some recommendations were made to the relevant authorities to improve the practice.